Natural product-based nanomedicine - Nurul Izzati, Azahar; Mohd Azmir, Arifin; Syed Mahmood, . (Scrivener Publishing, 2025)
Nanomedicine based on natural products is viable for developing a revolutionary therapeutic medium. Natural product extracts undergo several processes, such as screening, identification, biological synthesizing, compound isolation, and characterization. Natural products synthesized from various living organisms, such as plants, animals, marine organisms, and fungi, possess remarkable properties in the development of therapeutic agents such as (1) their potential as a lead compound in the development and production of drugs, (2) being a direct component in therapeutic and bioactive agents, (3) having compound isolation in nutraceutical production, (4) being a bioactive marker for spectroscopic and chromatographic analysis, and (5) having the potential to find new compounds. Nanomedicine is a drug delivery system designed to prevent, diagnose, image, and treat diseases. Nanomedicine unfolds from combining nanotechnology and active pharmaceutical ingredients (API). Natural product nanoparticle manufacturing allows alteration and is controlled by different aspects such as morphology, size, and aggregation conditions. Examples of polymer nanoparticles are polymer micelles, liposomes, and niosomes. Nanomedicine treatment applications include cancer, infectious diseases, neurological problems, cardiovascular diseases, and vaccines. In conclusion, future research and development must study possible toxicity and adverse reactions based on the in